PENGARUH KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA PADA SMPN 29 PADANG - Nofriwarti Nofriwarti; Afriyeni Afriyeni (STKIP Pesisir Selatan, 2026)
The success or failure of the world of education in achieving educational goals depends on the quality of teacher performance. Suboptimal teacher performance is influenced by professional ability, adequate compensation support, and high work motivation. This study aims to identify the direct and indirect effects of competence and compensation on teacher performance through work motivation as an intermediary variable. The research method used was quantitative with a population of 55 people, while the sampling technique applied was total sampling. Data collection methods included observation, interviews, questionnaires, and literature reviews. Data were analyzed with SEM-PLS using the SmartPLS 4 application. The results of the study showed that competence had a positive effect but was not able to directly improve teacher performance. However, competence was proven to be able to significantly increase teacher work motivation. In addition, compensation had a positive and significant effect on teacher performance and work motivation. Work motivation was also shown to have a positive and significant effect on improving teacher performance. The results of the study further showed that work motivation was able to mediate the influence of competence and compensation on teacher performance, making motivation an important factor in optimally improving the quality of teacher performance.